The arts of looking: visual arts from power to creativity - Vasconcelos, Flávia Maria de Brito Pedrosa (Farol, 2023)
This is a conference report organized to dialogue with the round table Creativity and perspectives in Contemporary Art within the Jornada Brasil of the Ibero-American Seminar on the Process of Creation – Poetics 2022. In this sense, it attempts to outline the universe of power and creativity and their connections as aesthetics and poetics in Visual Arts. Thus, it revisits memory and the history of looking in a narrative that brings its meanings from the archive of undergraduate and postgraduate teaching activities, listing the ways of perceiving, raising awareness and revising constructed.